MINERAL COMPOSITION OF HIGH-GRADE IRON ORES THAT ARE ONE OF THE COMPONENTSOF COARSE GRAINED SCREENINGS FROM CRUSHING AND SCREENING PLANTS IN THE KRYVYI RIH BASIN - Demchenko, O.; Evtekhov, V.; Georgiieva, H. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The deposits of high-grade iron ores of Kryvyi Rih basin are exploited by mines, the depth of mining operations takes up to 1200-1500 m. Due to the complexity of the configuration of ore deposits and to the lack of efficiency of ore extraction technologies, debris of the surrounding rocks, mainly hematite quartzites and schists, get into the lode rock. In this regard, the total content of iron in produced ore mass (52-54 mass.%) is significantly lower than the average content of the same figure in the ores occurring within contoured and prepared for exploitation deposits (about 57 mass.%). To improve the quality of marketable sinter ore, to increase the content of iron in its composition, the technology of three-stage crushing and three-stage screening for produced ore mass is used, which is implemented at the crushing and screening plants (CSP) of all seven mines of the basin. Fine-grained product of CSP with iron content up to 57-60 mass.% is sold on the global market of iron ore raw material. Coarse grained waste from CSP with a total iron content up to 40-46 mass.% (average index of about 42 mass.%) are stockpiled. Screenings from different mines CSP consist of the following components: high-grade hematite ore (7-10 mass.%), enriched hematite quartzite (5-7%), ordinary hematite quartzites (77-85%). Low ore and barren components of screenings are substandard hematite quartzites (1-2%), schists of different composition (0.5-1%), monomineral quartzites and vein quartz (about 0.5%). Occasionally fragments of diabase, amphibolite, and granite can be observed. Particles of high-grade iron ores represented by four mineral varieties such as: 1) micaceouse hematite-martite, martite; 2) dispersed hematite-martite; 3) martite-dispersed hematite; 4) dispersed hematite, kaolinite- dispersed hematite are the priority components of the screenings in terms of iron content. The iron content naturally decreases in the sequence of ores and is, in average, respectively, 64.83; 58.11; 55.65; 50.96 mass.%. The main ore-forming mineral is hematite, the amount of which varies from 72 mass.%. (dispersed hematite, kaolinite-dispersed hematite ores) to 92 mass.%. (micaceous hematite-martite, martite ores). Quartz (6-16 mass%) and kaolinite (0-10 mass.%) are of secondary importance. Other relict and newly formed silicates are represented in small quantities (up to 0.2 mass.%) as well as carbonates (up to 0.3 mass.%), and goethite (up to 0.2 mass.%). The presence of finely dispersed mineral phases (dispersed hematite, kaolinite) was determined using X-ray analysis. The research results are the basis for development of the technology for removing conditioned ore components with iron content 60-62 mass.% from CSP screenings by means of machine screening.